A COMPARISON OF SEVOFLURANE WITH MIDAZOLAM TO PROVIDE SEDATION TO PATIENTS FOR SURGERY UNDER LOCOREGIONAL ANAESTHESIA: Comparison of Sevoflurane with Midazolam - Janjua, Sarfraz Khan; Ahmad, Kaleem; Ahmad, Shafaq; Zaeem, Khalid; Tariq, Muhammad; Ishaque, Muhammad (Pakistan Armed Forces Medical Journal, 2008)
Objectives: To compare the quality, speed of recovery, and side effects of sevoflurane sedation compared with intravenous midazolam.Study Design: Quasi experimental, double-blind, comparative study.Place and Duration of study: Operation theatre complex, Combined Military Hospital Rawalpindi from 1st June 2006 to 31st Dec 2006.Patients and Methods: Total of sixty patients, American Society of Anaesthesiology I-III aged 18-70 years undergoing surgery under locoregional anaesthesia were divided into two equal groups by convenient sampling.Group A: (n=30)   received Sevoflurane sedation.Group B: (n=30)   received Midazolam sedation.The patients were sedated gradually during the procedure and maintained at Observer’s assessment of alertness and sedation (OAAS) score of 3. At recovery the OAAS score was measured at 5, 10 and 30 minutes after stopping the drug administration. Subjective assessment of quality of recovery was measured by visual analog scale (VAS) determined at baseline and 5, 10, and 30 min of recovery.Results: On observer’s assessment of alertness and sedation score no significant difference was observed between the two groups in the first 10 min after drug discontinuation but after 30 min all  patients  in group A and 26 out of 30 patients in group B had returned to an OAAS of 5 (p= 0.039). Subjective recovery as assessed by VAS scores showed that patients were more awake, had higher energy level, were less confused and better coordinated in group A sedation at 10 and 30 min post-procedure as compared to midazolam group B.Conclusion: Sevoflurane for sedation produced faster recovery as compared to intravenous midazolam measured by OAAS score and subjective assessment on VAS scale. However, sevoflurane is complicated by a high incidence of intra-operative excitement.